Sex work and COVID-19 in the New Zealand media: avoid the moist breath zone - Easterbrook-Smith, Gwyn (Bristol shorts research, 2023)
"New Zealand's relatively recent decriminalisation of sex work and its unusual success in combatting COVID-19 have both attracted international media interest. This accessibly-written book uses the lens of news media coverage to consider the pandemic's impacts on both sex workers and public perceptions of the industry. Analysing the stigmatisation of sex work in both short- and long-term contexts, the book addresses the impacts of intersectional oppressions or marginalisations on sex workers, and the ways sex work advocacy relates to other social justice movements. It unpicks how New Zealand's decriminalisation approach functions under stress, offering valuable information for advocates, activists and scholars."--Page 4 of cover